2010
DOI: 10.1124/jpet.110.167791
|View full text |Cite
|
Sign up to set email alerts
|

Orexins Depolarize Rostral Ventrolateral Medulla Neurons and Increase Arterial Pressure and Heart Rate in Rats Mainly via Orexin 2 Receptors

Abstract: An injection of orexin A or B into the cisterna magna or the rostral ventrolateral medulla (RVLM), where bulbospinal vasomotor neurons are located, elevated arterial pressure (AP) and heart rate (HR). We examined how orexins affected RVLM neurons to regulate cardiovascular functions by using in vitro recordings of neuronal activity of the RVLM and in vivo measurement of cardiovascular functions in rats. Orexin A and B concentration-dependently depolarized RVLM neurons. At 100 nM, both peptides excited 42% of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 38 publications
5
73
0
Order By: Relevance
“…One possibility is that orexin is directly influencing the SNS via activation of the brain stem premotor sympathetic regulatory brain regions within the rostral ventrolateral medulla, similar to that which is reported in SHR. 13,15 Orexin can activate ≈88% of adrenergic neurons within the rostral ventrolateral medulla of rats, 22 and it is these adrenergic bulbospinal neurons within the rostral ventrolateral medulla which are well known to influence sympathetic vasomotor tone. In addition, orexinergic neurons may directly activate the SNS via the sympathetic preganglionic neurons in the spinal cord.…”
Section: Sympathetic and Renin-angiotensin System Influencementioning
confidence: 99%
“…One possibility is that orexin is directly influencing the SNS via activation of the brain stem premotor sympathetic regulatory brain regions within the rostral ventrolateral medulla, similar to that which is reported in SHR. 13,15 Orexin can activate ≈88% of adrenergic neurons within the rostral ventrolateral medulla of rats, 22 and it is these adrenergic bulbospinal neurons within the rostral ventrolateral medulla which are well known to influence sympathetic vasomotor tone. In addition, orexinergic neurons may directly activate the SNS via the sympathetic preganglionic neurons in the spinal cord.…”
Section: Sympathetic and Renin-angiotensin System Influencementioning
confidence: 99%
“…Preclinical studies, mostly in rat, have focused on the cardiovascular effects of exogenously added orexins. In the majority of studies, central administration (intracerebroventricular or intracisternal) of extraphysiological doses of orexin peptides, particularly OX-A, acts to increase blood pressure and heart rate, although differences in experimental paradigms have also found unchanged or decreased cardiovascular parameters with orexin administration (Samson et al, 1999Shirasaka et al, 1999;Chen et al, 2000;White et al, 2006 ]OX-B and TCSOX 2 29 either partially or fully blocked the effects of exogenous orexins, suggesting that both receptor subtypes are involved (White et al, 2006;Samson et al, 2007;Huang et al, 2010). Direct administration to specific brain regions evoked either increases or decreases in blood pressure and heart rate, suggesting that stimulation of different structures may indeed differentially modulate cardiovascular function; however, differences in protocol, dose, and state of anesthesia probably also contribute to the disparate results (Chen et al, 2000;Antunes et al, 2001;Machado et al, 2002;Sato-Suzuki et al, 2002;Smith et al, 2002Smith et al, , 2007de Oliveira et al, 2003;Shahid et al, 2011).…”
Section: B Orexin Influences On Peripheral Physiologymentioning
confidence: 99%
“…In fact, the doses used in several of the studies is relatively high compared with the endogenous OX-A levels (0.2-0.4 pmol/ml) in rat CSF , and so the relevance to the role of intrinsic orexins in cardiovascular function is unknown. More relevant to the safety profile of orexin receptor antagonists in the clinic is the finding that central administration of the aforementioned OX 1 or OX 2 SORAs elicited no changes in heart rate or blood pressure when administered alone in preclinical models (Hirota et al, 2003;White et al, 2006;Samson et al, 2007;Huang et al, 2010;Shahid et al, 2011). Furthermore, preclinical studies in rats and dogs showed no effects on heart rate and blood pressure with oral administration of the dual orexin receptor antagonist, almorexant (ACT-078573) Furlong et al, 2009).…”
Section: B Orexin Influences On Peripheral Physiologymentioning
confidence: 99%
“…To our surprise, we failed to detect any significant rise in basal Ca 21 cyt levels when OXB was applied alone to the cultures, at concentrations that were protective for DA neurons. This is rather unexpected as OXB was reported to elicit robust calcium elevations and to cause sustained excitation of various neuronal cell types (Ishibashi et al, 2005;Nakamura et al, 2010), in particular through OX2R (Huang et al, 2010). In addition, the neuroprotective effect of NIC for DA neurons, which was unmasked here by OXB, was reported previously to be gated by Ca 21 cyt (Toulorge et al, 2011).…”
Section: Survival Promotion Of Dopamine Neurons By Orexinmentioning
confidence: 61%